The Impact of Collaborative Writing Strategy on EFL Students’ Writing Skills Through Adopting a Process-Based Approach - Khamouja, Abdessallam (International Journal of Language and Literary Studies, 2025)
Writing is one of the productive skills that involves communicating a message in the form of letters, words, and sentences. It is a mental effort of creating and inventing ideas, thinking about how to express them, and organizing them into paragraphs that a reader can understand. Effective writing requires effective writing strategies, such as the collaborative writing technique. The latter supports collaboration, critical thinking, and active participation towards producing a good piece of writing. The implementation of collaborative writing in the classroom requires students to be more active in all the processes of writing, such as brainstorming ideas, gathering and organizing information, drafting, revising, and editing. The main purpose of the present study is to examine teachers’ perceptions about the extent to which this writing technique can improve learners’ writing skills to produce an argumentative text. The findings indicate that the participants have a positive standpoint toward such a strategy because it develops students’ writing skills and increases their interaction. It also helps students stay focused on their goals by collaborating to create high-quality argumentative essays.